2019
DOI: 10.1002/fsn3.924
|View full text |Cite
|
Sign up to set email alerts
|

Application of steam explosion in oil extraction of camellia seed (Camellia oleifera Abel.) and evaluation of its physicochemical properties, fatty acid, and antioxidant activities

Abstract: This study evaluated the physicochemical properties of oils extracted from steam‐exploded camellia seed ( Camellia oleifera Abel.). Steam pressure, resident time, fatty acid composition, total phenolics, tocopherol, squalene, and sterol contents, and volatile compounds were determined. 1 H NMR and FTIR spectra were performed for the structure of camellia seed oil. This study has found the highest yield of oil was 86.56% and was obtained when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Yu and colleagues developed an extraction method based on water and were able to achieve better performance in the ABTS assay with this new method than with an organic solvent [ 40 ]. An unconventional work was also developed with and without steam explosion pre-treatment and the authors concluded that the steam explosion increased the DPPH scavenging activity of the extract [ 41 ]. Defatted seeds were also investigated in a study which compared the proficiency of isopropanol and butanol as extraction solvents being the best results obtained with isopropanol [ 42 ].…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Yu and colleagues developed an extraction method based on water and were able to achieve better performance in the ABTS assay with this new method than with an organic solvent [ 40 ]. An unconventional work was also developed with and without steam explosion pre-treatment and the authors concluded that the steam explosion increased the DPPH scavenging activity of the extract [ 41 ]. Defatted seeds were also investigated in a study which compared the proficiency of isopropanol and butanol as extraction solvents being the best results obtained with isopropanol [ 42 ].…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Camellia oleifera ( C. oleifera ), native to East Asia, is a valuable oilseed crop belonging to the genus Camellia of the Theaceae family 1 . It has been cultivated for more than 1000 years, with an annual output of seeds exceeding 2.4 million tons distributed over an area of 4.4 million hectares in China 2 .…”
Section: Introductionmentioning
confidence: 99%
“…SECSP and SECSO were obtained from camellia seed in our previous study, as described by Zhang et al. (2019a, 2019b), as shown in Supplementary Text. Pancreatin (CAS 8049‐47‐6, catalogue no.…”
Section: Methodsmentioning
confidence: 99%
“…(Tu et al ., 2017; Xiao et al ., 2017). Our previous study found that steam explosion pretreatment increased both oil extraction yield and bioactive compounds from camellia seed (Zhang et al ., 2019a). Moreover, steam‐exploded camellia seed oil (SECSO) exhibited higher antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%